PHYSICAL OCEANOGRAPHY CONDITION IN EASTERN KARIMATA STRAIT: PASIR MAYANG BEACH WEST KALIMANTAN - Harianto, Harianto; Kushadiwijayanto, Arie Antasari; Apriansyah, Apriansyah (Universitas Negeri Surabaya, 2018)
Karimata strait is located in the western Indonesian, separate the Kalimantan and Belitung island, that has an important role for the distribution services. The information about its dynamics such as tidal behavior, and wave is the key to support the navigation activities in this area. This research describes the results of measurements of the physical oceanography parameter on the eastern side of the Karimata Strait, Pasir Mayang Beach. The tidal data were measured for 15 days in February 25th ? March 12th, 2017 and sea current were observed for 24 hours on February 27-28th, 2017. The result showed that tidal type in this area is diurnal tide with amplitude of M2, S2, K1, and O1 respectively are 0.085 m, 0.086 m, 0.455 m, and 0.342 m. Significant wave?s high is ranged from 0.12 ? 0.31 m with significant period of 5.32-6.9 s. The wave direction is south western. The current velocity is ranged from 0.087- 0.112 m/s and average current velocity is 0.092 m/s. The tidal current direction is northeast at low tide and south western at high tide. This study also reveals important information that wave energy variability is not only affected by seasonal conditions but also influenced by tides. The tides have responsibility to change the propagation medium of wave that is originated dispersive to non-dispersive medium. This study opens a new study of correction of wave measurement procedures by including and taking into account the effects of tides.